Occupational burnout as a predictor of disability pension: a population-based cohort study. Issue 5 (18th November 2008) - Ahola, K; Gould, R; Virtanen, M; Honkonen, T; Aromaa, A; Lönnqvist, J
Abstract : Objectives: The aim of this study was to investigate whether burnout predicts new disability pension at population level during a follow-up of approximately 4 years. The diagnosis for which the disability pension was granted was also examined in relation to the level of burnout. Methods: We used a population-based cohort sample (n = 3125) of 30–60-year-old employees from an epidemiological health study, the Health 2000 Study, gathered during 2000–2001 in Finland. The data collection comprised an interview, a clinical health examination including a standardised mental health interview, and a questionnaire including the Maslach Burnout Inventory-General Survey. Disability pensions and their causes until December 2004 were extracted from national pension records. The association between burnout and new disability pension was analysed with logistic regression models adjusted for sociodemographic factors and health at baseline. Results: Altogether 113 persons were granted a new disability pension during the follow-up: 22% of those with severe burnout, 6% of those with mild burnout, and 2% of those with no burnout at baseline. After sociodemographic factors and health were adjusted for, each one-point increase in the overall burnout sum score was related to 49% increase in the odds for a future disability pension. A disability pension was most often granted on the basis of mental and behavioural disorders and diseases of the musculoskeletal system among those with burnout. After adjustments, exhaustion dimension among men and cynicism dimension among a combined group of men and women predicted new disability pensions. Conclusion: Burnout predicts permanent work disability and could therefore be used as a risk marker of chronic health-related work stress. To prevent early exit from work life, working conditions and employee burnout should be regularly assessed with the help of occupational health services.